2018
DOI: 10.3389/fpubh.2018.00318
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Sex and Sexual Experience in Predicting American Indian Adolescent Condom Use Intention Using Protection Motivation Theory

Abstract: Introduction: American Indian (AI) youth experience poor sexual health outcomes. Research indicates the Protection Motivation Theory (PMT) is a robust model for understanding how sexual risk and protective behaviors are associated with condom use intention (CUI). Studies indicate the constructs of the PMT which influence CUI vary by sex and sexual experience. This analysis explores associations between PMT constructs and CUI by sex and sexual experience among AI youth who participated in the Respecting the Cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
2
14
0
2
Order By: Relevance
“…Notably, media platform preferences and gender were found to be significantly associated with PV. According to the findings of a study by Rogers and Prentice-Dunn [ 39 ], a higher quantity of information can increase respondents’ PV scores, and Chambers et al [ 21 ] found that low vulnerability may be tied to a lack of knowledge about rabies risks factors and the inability to recognize one’s personal risk of rabies. Since YouTube is a popular media platform among students, it can be used to disseminate targeted informative videos according to their level of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, media platform preferences and gender were found to be significantly associated with PV. According to the findings of a study by Rogers and Prentice-Dunn [ 39 ], a higher quantity of information can increase respondents’ PV scores, and Chambers et al [ 21 ] found that low vulnerability may be tied to a lack of knowledge about rabies risks factors and the inability to recognize one’s personal risk of rabies. Since YouTube is a popular media platform among students, it can be used to disseminate targeted informative videos according to their level of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Using an ecological model (McLeroy et al, 1988) to frame sexual health influences, there are significant opportunities to intervene and promote healthy sexual behavior. Previous research supports a myriad of influences on American Indian adolescents’ sexual risk behaviors across levels of the social–ecological model including parent–adolescent communication and relationships (Saftner, 2016), peer norms (Chambers et al, 2018; Saftner, Martyn, Momper, Loveland-Cherry, & Low, 2015), perceived impact of risky sexual behavior (Chambers et al, 2018), intention to have sex (Tingey et al, 2018), and condom use self-efficacy (Tingey et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, research on condom use intention of young people has caused more concern. [ 35 , 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] However, another study indicated no association of condom use self-efficacy and condom use intention. [ 36 ] The contradiction was possibly caused by the different study populations and different theories of health behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation